Organizational cultural factors hindering women ascending to top management positions in public universities in Kenya: a case of Moi University - Makori, Rebecca S.; Onyango, Maria; Attyang, Judith Miguda; Bantu, Edward; Onderi, Peter Omae (IISTE, 2011)
It is observed that the major setback to economic development in Kenya is stagnation in industrial development. To overcome these, Kenya plans to be a middle level income nation by the year 2030. These plans are to be realized through “Vision 2030”. To achieve these goals, Kenya requires gender mainstreamed team of highly skilled workers with competency in administration and strategic management. Kenya has to prepare at least twice as many women graduates with administration and management background to match the male counterparts even in the stipulated 1/3 ratio. Globally, women experience many challenges in ascending to top management positions especially in institutions of higher learning. This is despite endless calls and legislations to push for gender equity in appointments to both junior and top management positions in all departments of our institutions. This study aimed to determine the influence of organizational culture on women ascending to top management positions, to determine the effects of social factors on women ascending to top management positions and the effects of demographic factors on women ascending to top management positions. The target population was of 114 out of whom 34 was sampled. Semi structured questionnaires were used to collect primary data. Secondary data was collected from document reviews. The primary data collected was analyzed using computer supported software and presented using descriptive statistics. The Computer aided program was used (SPSS Version 22.0 for analyzing quantitative data. The study findings established that organizational culture hindered women ascending to top management position. It was concluded that the University Management should adopt policies that will ensure gender equality and equity in the appointments and promotions in leadership positions be considered. In addition, the study concluded that gender discrimination hindered women ascending to top leadership roles. The study recommended that University should develop and implement policies that are harnessing gender equity in the appointments and promotion of staff. Keywords: Gender balance, Organizational culture, Equal opportunities.